Strategic Planning as an Organization Design Exercise. Issue 6 (14th July 2015) - Roth, William F.
<x xml:space="preserve">Abstract</x> The major challenge faced by modern day strategic planning efforts is the accelerating rate of change in both the internal and external environments. Most companies are bogged down in traditional approaches that take too long, lack the required flexibility, and produce results that are frequently obsolete before they are implemented. Interactive planning, with its core concept of idealized design, focuses initially on shaping an organization capable of learning continually and adapting so that the improvements implemented make sense.